KETERBACAAN WACANA DALAM BUKU TEKS BAHASA INDONESIA “EKSPRESI DIRI DAN AKADEMIK” CETAKAN KEDUA MELALUI CLOZE TEST SISWA KELAS X SMAN 1 MAKASSAR - Khairil Khairil; Slam Salam; Andi Fatimah Junus (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract. The Readability of the Indonesian Textbook Discourse "Ekspresi Diri dan Akademik" Second Edition Using Cloze Test Methode On Grade X SMAN 1 Makassar. This research aimed to describe the readability of discourse in the Indonesian textbook "Ekspresi Diri dan Akademik" Second Edition on grade X SMAN 1 Makassar. The method used in this research is a quantitative survey methods that describe the readability level of the Indonesia textbook "Ekspresi Diri dan Akademik" Second Edition on grade X at SMAN 1 Makassar. The population of this research was all students of grade X at SMAN 1 Makassar. Sampling on this population was selected by using cluster random sampling. The sample in this research there were two classes, X MIA 5 and X IIS 3. Data collection techniques in this research is the cloze test. Data obtained using the formula cloze test. The results showed that out of the eight tested discourse to the students there are six discourse that is at the readability level independent/easy. There is a discourse belonging to the category of reading level instructional/medium. Average readability level was 68% overall discourse in the category reading level independent/easy, indicating that the level of discourse is very high readability. Results like that makes the discourse in the Indonesian Textbooks "Ekspresi Diri dan Akademik" Second Edition on grade X published by the Ministry of Education and Culture is not good enough to be used as teaching materials.